Organizational Correlates of Perceived Role Performance at the University and College Level - Harrison, Frank (Academy of Management Journal, 1973)
An empirical study relates the perceived role performance of 155 faculty members in ten business schools of medium-sized universities and colleges in the Pacific Northwest to the organic system of management as conceived by Burns and Stalker. The findings indicate that the greater the "organicity" of the system of management the higher the perceived role performance of the individual faculty member.